Decreased surface blistering and deuterium retention in potassium-doped tungsten exposed to deuterium plasma following ion irradiation. (1st February 2023) - Ma, Xiaolei; Zhang, Xiaoxin; Wang, Ting; Gao, Yuan; Yuan, Yue; Cheng, Long; Zhu, Jipeng; Lv, Wei; Lang, Shaoting; Ge, Changchun; Yan, Qingzhi
Abstract: A large-size potassium-doped tungsten (KW) plate with a thickness of 15 mm was fabricated via powder metallurgy technology and hot rolling. In order to appraise the irradiation resistance of KW, the surface deuterium (D) blistering and D retention were studied on Fe 11+ pre-damaged (0, 0.05 and 0.5 dpa) KW and pure tungsten (PW), which were exposed to ∼60 eV and ∼5 × 10 21 m −2 s −1 D plasmas at 500 K at a fluence of ∼5.76 × 10 25 m −2 . The results indicate that the KW alloy can better inhibit the generation of vacancy defects after Fe 11+ ion damage compared with PW because K bubbles can restrain the migration of W self-interstitial atoms and the accumulation of vacancies caused during Fe 11+ ion irradiation. The Fe 11+ ion pre-damage can relieve the surface blistering and D retention of PW and KW at the same time, and the KW has a better effect of inhibiting D retention, while it does not show a significant advantage in inhibiting surface blistering compared with PW. In addition, the causes of the discrepancy in total D retention and the surface morphology evolution of PW and KW are discussed in detail.